A new and commercial species of Gastrosaccus Norman, 1868 (Peracarida: Mysida: Mysidae) from Java, Indonesia - Bamber, Roger N; Morton, Brian (Zootaxa, 2012)
A new species of gastrosaccid mysid, Gastrosaccus yuyu, is described from the higher tidal levels of wave-exposed surfbeaches of Java, Indonesia. It belongs to that group of Gastrosaccus species with a fringe of slender spine-like filamentsalong the posterodorsal margin of the carapace, and, in having a mid-dorsal apophysis on the fifth abdominal somite inthe adult and filaments which extend onto the postero-lateral lobes of the carapace, is close only to G. sorrentoensis. It isdistinct in having fewer marginal carapace filaments than G. sorrentoensis, as well as apical telson spines which are hardlylonger than the sub-apical lateral spines and are separated from those spines by a gap distinctly larger than those betweenthe previous spines, a more pronounced rostrum, and a distinct conformation of the distal tip of the mandibular palp, interalia. Gastrosaccus yuyu is collected commercially by artisanal fishermen in Java, and cooked into a fried rice-flour crisp biscuit, known locally as “peyek”.